Advances in hematopoietic cell transplant for the treatment of hematologic malignancies. Issue 1 (February 2019) - Taraseviciute, Agne; Pulsipher, Michael A.
Abstract : Purpose of review: Incorporation of minimal residual disease (MRD) testing in acute lymphoblastic leukemia (ALL) and acute myeloblastic leukemia (AML) has transformed the landscape of hematopoietic cell transplantation (HCT). Pre-HCT MRD has allowed prognostication of HCT outcomes for high-risk leukemia patients, whereas the detection of post-HCT MRD has allowed for interventions to decrease relapse. Recent findings: In this review, we emphasize studies from the past two decades that highlight the critical role of MRD in HCT in pediatric ALL and AML. Advances in MRD detection methodology, using next-generation sequencing, have improved the sensitivity of MRD testing allowing for more accurate predictions of HCT outcomes for patients with relapsed and refractory ALL and AML. In addition, novel pre-HCT therapies, especially immunotherapy in ALL, have dramatically increased the number of patients who achieve MRD-negative remissions pre-HCT, resulting in improved HCT outcomes. Post-HCT MRD remains a challenge and new therapeutic interventions are needed to reduce post-HCT relapse. Summary: As immunotherapy increases pre-HCT MRD-negative remissions, and next-generation sequencing-MRD is incorporated to improve the sensitivity of MRD detection, future clinical studies will investigate less toxic HCT approaches to reduce long-term sequelae and to identify which patients may benefit most from early post-HCT intervention to reduce relapse.